External validation test of body height estimation on outpatient radiotherapy clinic of Dr. Cipto Mangunkusumo General Hospital - Wiji Lestari; Fiastuti Witjaksono; Nurul Ratna Mutu Manikam; Wahyu Ika Wardhani; Krisadelfa Sutanto (World Nutrition Journal, 2023)
Background : Stature is required to calculate body mass index and determine the energy needs of patients in nutritional medical therapy. Difficulty was found to obtain stature data in patients who are unable to stand. Therefore, there are some height estimation formula to predict the actual height using knee height. This study aimed to validate the Chumlea formula on outpatient clinic of Dr. Cipto Mangunkusumo General Hospital, Indonesia. Methods : This cross-sectional study used 90 respondents selected by consecutive sampling. Actual height, knee height, age and gender data were collected. Estimated height using the three of Chumlea formula. Pearson correlation was used to see the correlation between actual height and estimated height. Paired t-test were used to determine the difference significance. Results : The average age of the subjects was 45±10 years old with actual height 157±10 cm, and knee height 48.8±3.5 cm. A strong positive correlation was found between actual height with all estimated height on male (p=0.000; r > 0.8) and female subjects (p=0.000; r > 0.6). However, comparison between actual height and estimated height showed no significant differences only in Chumlea L1 formula (p=0.087) and Chumlea L3 formula (p=0.824) on the male subjects. Conclusions : Chumlea L1 and Chumlea L3 formula was a valid fomulation for calculating the estimated body height in adult male patients. There was no valid Chumlea’s formulation to estimate body height in female patients.